A scoping review on the significance of programmed death-ligand 1-inhibiting microRNAs in non-small cell lung treatment: A single-cell RNA sequencing-based study - Shadbad, Mahdi Abdoli; Ghorbaninezhad, Farid; Hassanian, Hamidreza; Ahangar, Noora Karim; Hosseinkhani, Negar; Derakhshani, Afshin; Shekari, Najibeh; Brunetti, Oronzo; Silvestris, Nicola; Baradaran, Behzad (Frontiers in Medicine, 2022)
Background The programmed death-ligand 1 (PD-L1)/PD-1 axis is one of the well-established inhibitory axes in regulating immune responses. Besides the significance of tumor-intrinsic PD-L1 expression in immune evasion, its oncogenic role has been implicated in various malignancies, like non-small cell lung cancer (NSCLC). As small non-coding RNAs, microRNAs (miRs) have pivotal roles in cancer biology. The current study aimed to systematically review the current knowledge about the significance of PD-L1-inhibiting miRs in NSCLC inhibition and their underlying mechanisms. Materials and methods We conducted the current scoping review based on the PRISMA-ScR statement. We systematically searched Embase, Scopus, Web of Science, PubMed, Ovid, EBSCO, ProQuest, Cochrane Library, African Index Medicus, and Pascal-Francis up to 4 April 2021. We also performed in silico tumor bulk RNA sequencing and single-cell RNA sequencing to further the current knowledge of the non-coding RNA-mediated tumor-intrinsic PD-L1 regulation and the PD-L1/PD-1 axis in NSCLC. Results The ectopic expression of hsa-miR-194-5p, hsa-miR-326, hsa-miR-526b-3p, hsa-miR-34a-5p, hsa-miR-34c-5p, hsa-miR-138-5p, hsa-miR-377-3p, hsa-let-7c-5p, hsa-miR-200a-3p, hsa-miR-200b-3p, hsa-miR-200c-3p, and hsa-miR-197-3p, as PD-L1-inhibiting miR, inhibits NSCLC development. These PD-L1-inhibiting miRs can substantially regulate the cell cycle, migration, clonogenicity, invasion, apoptosis, tumor chemosensitivity, and host anti-tumoral immune responses. Based on single-cell RNA sequencing results, PD-L1 inhibition might liberate the tumor-infiltrated CD8+ T-cells and dendritic cells (DCs)-mediated anti-tumoral immune responses via disrupting the PD-L1/PD-1 axis. Conclusion Given the promising preclinical results of these PD-L1-inhibiting miRs in inhibiting NSCLC development, their ectopic expression might improve NSCLC patients’ prognosis; however, further studies are needed to translate this approach into clinical practice.